Risk of psychiatric diseases among patients with psoriasis in Korea: A 12‐year nationwide population‐based cohort study. Issue 11 (30th August 2021) - Oh, Jongwook; Jung, Keum Ji; Kim, Tae‐Gyun; Kim, Hae Won; Jee, Sun Ha; Lee, Min‐Geol
Abstract: The association between psoriasis and risk of psychiatric diseases has not been thoroughly evaluated in a large longitudinal cohort of the Asian population. We conducted a nationwide cohort study encompassing more than 1.6 million Koreans with a 12‐year follow‐up period. Patients were considered to be in the psoriasis cohort if they had an incident diagnostic code for psoriasis and included patients were followed up until they developed any psychiatric disease. In adjusted models, psoriasis patients (n = 10 868) were at an 18% increased risk for depression (hazard ratio [HR], 1.18; 95% confidence interval [CI], 1.09–1.26), 16% for anxiety disorders (HR, 1.16; 95% CI, 1.08–1.26), and 21% for somatoform disorders (HR, 1.21; 95% CI, 1.08–1.34) compared with the referent cohort ( n  = 1 620 055). Patients with moderate‐to‐severe psoriasis had a higher risk of developing depression and somatoform disorders than patient with mild disease (depression, HR, 1.28; 95% CI, 1.07–1.54 vs HR, 1.17; 95% CI, 1.07–1.27; somatoform disorders, HR, 1.60; 95% CI, 1.26–2.03 vs HR, 1.13; 95% CI, 1.00–1.28). Our results highlight the burden of psychiatric diseases in patients with psoriasis in Korea and suggest that appropriate medical support for possible mental illness is warranted in Asian psoriatic patients.